Peculiarities of studying verbs of motion in the course "Ukrainian Language for International Students" in engineering and pedagogical education - Rotova , N. (Problems of Engineer-Pedagogical Education, 2023)
Changes in recent years in the system of higher education in Ukraine, the entry of Ukrainian free education into a single global educational space, and the need to use distance education require rethinking the goals and objectives of education, and learning strategies in various fields of science. The task of a Ukrainian language teacher is not only to teach international students the language system of the Ukrainian language, which includes phonetics, vocabulary and grammar, but also to develop their ability to properly assess the communicative situation when interacting with native speakers, read cultural codes contained in Ukrainian, and adequately perceive signals of nonverbal communication (gestures, facial expressions, etc.) of the interlocutor. In addition to reception, the purpose of teaching the Ukrainian language is to form a willingness to produce speeches in accordance with the cultural, etiquette and language norms of the Ukrainian linguistic and cultural community. Given the processes occurring in teaching methods, we have proposed a systematic way of learning movement verbs at the initial stage of learning, which in a strict time limit allows not only facilitating the perception of educational material, but also increasing the rate of grammar, communication and study skills acquisition. According to many scholars, the verb itself is the most complex grammatical category of the Ukrainian language, as it occupies the central place in the semantic structure of the sentence. At the first stage, when students study the accusative case, the verbs йти, ходити, піти are introduced and the peculiarities of their use are clarified; later, the verbs їхати, їздити, поїхати are introduced with an explanation about the differences in the ways of performing the action: йти пішки, but їхати на автобусі, машині, etc. At the second stage, the basic verbs of movement without prefixes are studied. It is advisable to introduce this topic at the end of the elementary course, when the basic values of cases have been mastered. When studying the basic verbs of motion without prefixes, a list of relative verbs of unidirectional and multidirectional motion is given and the differences in the nature of motion are explained. At the third stage, verbs of movement with prefixes are studied. On the basis of the previously considered verbs, derivatives are formed, the meaning of which depends on the word-building prefix. At the fourth stage, figurative meanings of movement verbs are studied. This stage requires students to be fluent in the Ukrainian language. On the basis of the language material used in classes, monologue language skills are formed as well as the ability to convey the gist of a short text which students read or listen to. Tasks for texts are aimed at checking the material to be actively assimilated, which involves answering questions, composing dialogues, retelling texts, etc. The proposed approach promotes the rapid assimilation of the meaning of movement verbs and the correct use of the chosen form in a particular speech situation. Clear organization of educational materials and logically sustained step-by-step and stage-by-stage deployment help remove psychological barriers in a short time, activate the knowledge acquired, generate interest and stimulate motivation to learn the Ukrainian language.